If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12x + -23 = 7 Reorder the terms: -23 + 3x + 12x = 7 Combine like terms: 3x + 12x = 15x -23 + 15x = 7 Solving -23 + 15x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 15x = 7 + 23 Combine like terms: -23 + 23 = 0 0 + 15x = 7 + 23 15x = 7 + 23 Combine like terms: 7 + 23 = 30 15x = 30 Divide each side by '15'. x = 2 Simplifying x = 2
| 4x-7+4x=4-3x | | -132m-36-6m=-36-5m | | -5t(2s+9)= | | 8+6n+2n+10= | | 9+5x=3x+11 | | x/7=-5/1 | | 3x+12x-23= | | 8r(2s-4)= | | 0=5x-85 | | 1-9r+r-8= | | 3x-2(x+2)=3x-(2-2x)4 | | 9x-59=-149 | | 39-9x=-24 | | -6c-66=0 | | 6x-35=37 | | -5+49x+21=-42-9x | | (-2x+10)*4y= | | s(t)=64t-16x^2 | | -9+9x=27 | | 300x+600y=2700 | | 24+6x=102 | | 48+8x=120 | | 5(t+1)=4t | | (-5)-4x=21 | | 60-90k+9k=60+9k | | 4(2m+6)= | | 21x+y-5x+3(x+2y)= | | -25=-10+3x | | 22=-4x+6 | | 10x-9+17x-12= | | 9(3x+5)-7x=4(5x+6)+19 | | 4(5x+1)-14x= |